Home-School Communications: Multicultural Parents of Children with Disabilities - Abadeh, Heidi (International Journal about Parents in Education, 2023)
The primary goal of this study was to examine the role of communication between parents of children with special needs and schools. As the multicultural population in United States’ schools continues to increase, the need to help teachers understand what parents expect in terms of being able to communicate effectively grows in importance. Understanding cultural expectations of parents is important for teachers to communicate effectively. Parents of children with disabilities may be unsure of their role in their children’s education, especially if they were educated in schools outside of the United States. By designing and implementing effective communication programs for parents of students with disabilities, conflict that may arise between parents and school officials can be avoided.